2021
DOI: 10.3390/ijerph18094818
|View full text |Cite
|
Sign up to set email alerts
|

Personality Prototypes in People with Type 1 Diabetes and Their Relationship with Adherence

Abstract: Type 1 diabetes (Dm1) is a chronic endocrine and metabolic disease that affects the whole person and requires active, decisive treatment. However, personality traits may influence a patient’s adherence to treatment guidelines. The objective of this work is firstly to identify the 3 Asendorpf personality prototypes (resilient, undercontrolled and overcontrolled) in a sample of Dm1 individuals and determine whether there are any differences in comparison with a control sample; and, secondly, to study their assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…12,13 The current study reported higher HbA1c and FBG in diabetic children than in controls, which is in alignment with other studies. 10,14,15 When the conditions are physiologically favourable, proteins are regularly glycated during numerous biochemical reactions. Glycation of Hb, on the other hand, occurs through a non-biochemical reaction between the N-terminal end of the chain and glucose, resulting in the formation of a Schiff base.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 The current study reported higher HbA1c and FBG in diabetic children than in controls, which is in alignment with other studies. 10,14,15 When the conditions are physiologically favourable, proteins are regularly glycated during numerous biochemical reactions. Glycation of Hb, on the other hand, occurs through a non-biochemical reaction between the N-terminal end of the chain and glucose, resulting in the formation of a Schiff base.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the Neuroticism domain includes anxiety, angry hostility, depression, self-consciousness, impulsiveness, so it would be important in future studies to asses associated factor components to make a more in depth analysis of those aspects of personality, concerning also possible psychopathology. Also, other psychological factors are worth to be taken into account in analyzing metabolic control [35,36]. Such studies are now in progress in our Clinic.…”
Section: Limitationsmentioning
confidence: 98%
“…The individual differences in the development of adherence patterns are well observed under the scope of this research. A special contribution was made by (Sánchez et al, 2021) who investigated the personality prototypes and their relationship with the adherence of patients suffering from type 1 diabetes. For personalized care, a complete understanding of personality prototypes is necessary as highlighted by this research.…”
Section: Personality Traits As Predictors Of Adherencementioning
confidence: 99%